2011
DOI: 10.1136/gutjnl-2011-300509
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine-driven lymphocyte infiltration: an early intratumoural event determining long-term survival in resectable hepatocellular carcinoma

Abstract: ObjectiveHepatocellular carcinoma (HCC) is a heterogeneous disease with poor prognosis and limited methods for predicting patient survival. The nature of the immune cells that infiltrate tumours is known to impact clinical outcome. However, the molecular events that regulate this infiltration require further understanding. Here the ability of immune genes expressed in the tumour microenvironment to predict disease progression was investigated.MethodsUsing quantitative PCR, the expression of 14 immune genes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
266
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(280 citation statements)
references
References 45 publications
14
266
0
Order By: Relevance
“…Thus, in patients with early-stage HCC, an immune gene signature associated with T-cell and NK-cell infiltration in resected HCC tissue was predictive of better survival (32). Toll-like receptor 3 expression that correlated with the degree of NK-cell infiltration was also a favorable predictor (33).…”
Section: Discussionmentioning
confidence: 92%
“…Thus, in patients with early-stage HCC, an immune gene signature associated with T-cell and NK-cell infiltration in resected HCC tissue was predictive of better survival (32). Toll-like receptor 3 expression that correlated with the degree of NK-cell infiltration was also a favorable predictor (33).…”
Section: Discussionmentioning
confidence: 92%
“…It has been demonstrated that tumor-infiltrating immune cells play an important role in host immune defense against tumor progression in various cancers. [8][9][10][11] These observations seem to provide a reasonable treatment direction and impel an increasing number of researchers to focus on immune responses in the tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…8,17 Furthermore, NK cell-related genes are closely associated with NK cell function, and data from microarray experiments suggest that a series of NK cell-associated genes accurately predicts the clinical outcome of HCC patients, especially in early stages. 8 NK cells express a large number of immune recognition receptors (NKRs) to recognize ligands on hepatocytes, liver sinusoidal endothelial cells, stellate cells and Kupffer cells, which maintain the balance between immune response and immune tolerance of NK cells. One particular strategy that tumors have to escape the immune system is to target receptor-ligand systems to impair NK cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Regulatory T cells, Kupffer cells (resident liver macrophages) and other TAMs impair cytotoxic T cell activities and their anticancer functions. Accordingly, several studies reported associations of decreased intratumoral densities of NK cells, low cytotoxic T, high TAM density and high regulatory T cell numbers with better pathological features and worse prognosis in HCC patients [19][20][21][22]. Recent studies have proven the importance of TAMs in HCC proliferation and survival [14,15,18,21,23,24].…”
Section: Tumor Microenvironment and Tumor-associated Macrophages In Hmentioning
confidence: 99%